Carbon nanotube circuits in the presence of carbon nanotube density variations - Zhang, Jie; Patil, Nishant; Hazeghi, Arash; Mitra, Subhasish (2009 46th ACM/IEEE Design Automation Conference, 2009)
Carbon Nanotubes (CNTs) are grown using chemical synthesis. As a result, it is extremely difficult to ensure exact positioning and uniform density of CNTs. Density variations in CNT growth can compromise reliability of Carbon Nanotube Field Effect Transistor (CNFET) circuits, and result in increased delay variations. A parameterized model for CNT density variations is presented based on experimental data extracted from aligned CNT growth. This model is used to quantify the impact of such variations on design metrics such as noise margin and delay variations of CNFET circuits. Finally, we analyze correlation that exists in aligned CNT growth, and demonstrate how the reliability of CNFET circuits can be significantly improved by taking advantage of such correlation.